A Four-Year Study of Antibiotic Resistance, Prevalence and Biofilm-Forming Ability of Uropathogens Isolated from Community- and Hospital-Acquired Urinary Tract Infections in Southern Italy - Marilena Trinchera; Angelina Midiri; Giuseppe Mancuso; Maria Antonietta Lagrotteria; Carmelo Antonio De Ani; Carmelo Biondo (Pathogens)
The aim of this study was to investigate the differences between nosocomial and community microorganisms isolated from patients with UTI by determining their bacterial profile, antibiotic resistance and ability to produce biofilms. A retrospective study, based on bacterial isolates from consecutive urine samples collected between January 2019 and December 2023, was conducted at a university hospital. The main pathogens isolated from both community and hospital samples were the same, but their frequency of isolation differed. Compared with community-associated cases, hospital-associated infections have more isolates of Acinetobacter baumanii complex. In contrast, Proteus mirabilis isolates were more prevalent in community than in hospital infections. In both hospital and community isolates, gram-positive bacteria showed a lower overall antimicrobial resistance (22%) compared to gram-negative bacteria (30%). The data demonstrated that individual strains exhibited disparate degrees of capacity for biofilm formation. Additionally, the data indicate an inverse correlation between biofilm production and antibiotic resistance. Isolates from community patients exhibited lower capacities for biofilm production in comparison to the capacities demonstrated by microorganisms isolated from nosocomial patients (29% and 35%, respectively). Area-specific surveillance studies can provide valuable information on UTI pathogens and antimicrobial resistance patterns, which can be useful in guiding empirical treatment.